ANALISA RISIKO KECELAKAAN KERJA PADA PROYEK KONSTRUKSI JEMBATAN MUSI VI PALEMBANG - Suparman, Suparman; Fitriani, Heni (Jurusan Teknik Sipil & Perencanaan Fakultas Teknik Universitas Sriwijaya, 2016)
Occupational Safety and Health (K3) issues in Indonesia are still often neglected. This is because all parties involved in the construction project from the highest level of project leader to the lowest level such as rough labor, still pay less attention on the Occupational Safety and Health (K3) in every stage of construction work. In this research will be investigated the occupational accident risk, occupational accident risk assessment, and occupational accident risk management, so it can be proposed mechanism of occupational accident risk control at construction project of Musi Bridge VI Palembang. Occupational accident risk identified through interviews and observation. Risk assessment is determined by questionnaire. Risk assessment refers to a method of AS / NZS 4360: 2004 to determine the level of risk. Risk control using Job Safety Analysis (JSA). Data processing shows that there are 64 occupational injury risks, i.e., 13 low risk, 47 medium risk, and 4 high risk. It can be concluded that the highest risk factor for the workers is inhaled the welding smoke with the risk index of 16. Workers are required to use PPE in accordance with the type of work, strict supervision of workers in the usage of PPE, checking the work environment (safety patrol) on a regular basis, safety talk every week, installation of safety signs and workerâs health inspection.